The taste of blood : spirit possession in Brazilian Candomblé - Wafer, James William, 1948- (Contemporary ethnography series., 1991)
Enter the fascinating world of the Condomble regions of Brazil, where interaction between spirits and human is considered an everyday occurrence. Jim Wafer uncovers the social life, rituals, folklore, and engaging personalities of the villagers of Jacari, among whom trances, sorcery, and spirit possession demonstrate the coexistence of different kinds of reality. This ethnography is intriguing not only because of the originality of its approach to the more enigmatic aspects of another culture but also because it uses insights gained from participation in that culture to reflect on the paradoxes inherent in the writer's own culture, and in the human condition in general. -- Publisher description.